A produção científica sobre currículo na educação profissional técnica de nível médio: foco no curso de informática - Almeida, Alexandre Marchiori de (2020)
This dissertation presents the results of a bibliographic research on the curriculum in technical vocational education of medium level between the period of 2008 and 2018. Based on authors such as Ferreira (year), Frigotto (year), Sacristán (year), Ramos (year), Romanelli (year), Schwartzman (year), among others, has historically contextualized professional education in Brazil. Initially, the history of the Paula Souza State Technological Education Center is presented and then the theses and dissertations that address the curriculum in technical education at the technical level are presented. The methodology applied in the research is exploratory, with a qualitative and quantitative approach, in the scientific works available in the national depository of the Brazilian Digital Library of Theses and Dissertations with themes based on scientific production on curriculum in technical professional education at the secondary level, focusing on the Computing. From the national depositary of the Brazilian Digital Library of Theses and Dissertations, within an initial analysis with more than 170 works, it was possible to identify 35 academic-scientific productions that investigate the theme of professional education and curriculum. From the careful reading of the abstracts, nine papers were selected that specifically address the curriculum in technical vocational secondary education. The results obtained indicate the relevant authors in the field of professional education, pointing to thematic categories constituted by the researchers, who present professional and technical education, curriculum, technical vocational education of secondary level, professional training, technical training of secondary level, teacher training , integrated curriculum, education, work and technical curriculum in professional education. It appears that the majority of productions investigates the curricular integration resulting from the guidance of Decree nº 5.154 / 2004 and of Laws nº 11.741 / 2008 and nº 13.415 / 2017, which allowed curricular flexibility and the proposition of varied training processes, in addition to addressing the challenges, limits and difficulties in the implementation of the National Curriculum Guidelines for Technical Vocational Education at Middle Level - Opinion nº 11/2012 and Resolution nº 6/2012. Therefore, the investigations carried out in the research allow the analysis of the works and the understanding of the scientific knowledge about the curriculum in technical professional education of medium level in the axis of the course of Informatics.